Determinants of Entrepreneurial Intention: Case of Students at Moulay Ismail University of Meknes - JENANE, Hanane; ACHOUR, Fatima Zahra (Revue Internationale des Sciences de Gestion, 2024)
In recent decades, we have witnessed a proliferation of entrepreneurship education programs. In this regard, the university plays a crucial role in developing entrepreneurial skills, creativity, and innovation, thus stimulating students' entrepreneurial spirit. The objective of this article is to study the influence of entrepreneurship education on the entrepreneurial intention of students at Moulay Ismail University in Meknes. We also take into account the influence of psychological, contextual, and sociocultural factors for understanding their entrepreneurial intention comprehensively. The study of this issue draws on Shapero and Sokol's (1982) social dimensions of entrepreneurship model and Ajzen's (1991) theory of planned behavior. The chosen method involves testing a model of intention inspired by Tounès (2006). Accordingly, we analyze entrepreneurial intention, considering three sets of factors: attitudes toward the behavior, subjective norms, and perceived behavioral control. The results indicate that only attitudes toward students' behavior and perceived behavioral control are significant in explaining entrepreneurial intention.